Mixed cropping systems in cardamom (Elettaria cardamomum Maton) - An analysis - KRISHNAKUMAR, K SRINIVASAN, SIDDAGANGAIAH SIDDAGANGAIAH, A K BISWAS, V (Journal of Spices and Aromatic Crops, 1999)
Surveys and economic analyses conducted in various cardamom (Elettaria cardamomum) plantations adopting mixed cropping systems in Kerala and Karnataka, India indicated that inclusion of black pepper (Piper nigrum) or coffee (Coffea arabica) and arecanut (Areca catechu) was highly renumerative giving high cost-benefit ratios.